2008
DOI: 10.1080/13693780801961352
|View full text |Cite
|
Sign up to set email alerts
|

Fusariumkeratitis and contact lens wear: facts and speculations

Abstract: Over the past several decades mycotic keratitis has been considered a rare sequel to hydrogel contact lens wear. In 2005--2006 an upswing in the incidence of Fusarium keratitis was associated with a disproportionate use of one multipurpose contact lens solution (MPS, ReNu with MoistureLoc, Bausch & Lomb, Rochester, NY). The MPS, as manufactured and marketed, was sterile and met regulatory guidelines for antimicrobial activity. A multivariant interaction of poor hygienic practices and the contact lens paraphern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 69 publications
1
32
0
1
Order By: Relevance
“…25 The recent outbreaks of fungal and Acanthamoeba keratitis associated with specific multipurpose contact lens disinfecting solutions has highlighted these as causative agents of disease during contact lens wear. 26,27 Although the rate of contact lens related Fusarium keratitis slowly decreased after withdrawal of the solution, 10 the overall incidence of Acanthamoeba keratitis remained higher than prior to the epidemic. 10,28 The incidence of fungal or amoebal keratitis during lens wear still remains much lower than for bacterial keratitis 1,4 but these continue to be difficult infections to diagnose and manage.…”
Section: Resultsmentioning
confidence: 99%
“…25 The recent outbreaks of fungal and Acanthamoeba keratitis associated with specific multipurpose contact lens disinfecting solutions has highlighted these as causative agents of disease during contact lens wear. 26,27 Although the rate of contact lens related Fusarium keratitis slowly decreased after withdrawal of the solution, 10 the overall incidence of Acanthamoeba keratitis remained higher than prior to the epidemic. 10,28 The incidence of fungal or amoebal keratitis during lens wear still remains much lower than for bacterial keratitis 1,4 but these continue to be difficult infections to diagnose and manage.…”
Section: Resultsmentioning
confidence: 99%
“…Deletion of the veA ortholog gene in Fusarium verticillioides induced yeast-like growth similar to microcycle conidiation (19), and a Fusarium solani mutant with continuous microcycle conidiation has been reported (78). Microcycle conidiation is regarded as a key factor in the development of Fusarium keratitis disease by several Fusarium spp., such as Fusarium oxysporum and F. solani, because rapid fungal amplification is guaranteed by this process (79). However, microcycle conidiation had not been observed in F. graminearum, suggesting that this process is normally suppressed in F. graminearum.…”
Section: Figmentioning
confidence: 97%
“…It is tempting to suggest that F. oxysporum is much more resistant to certain MPSs, and this probably explains its overwhelming presence among the isolates from the recent outbreak (3,8,21). An insight into this observed phenomenon has been provided in studies by Ahearn and colleagues, who reported that F. oxysporum strains showed greater penetration of contact lenses and survived better after treatment with MPS, while F. solani strains were easily removed (2,35). However, these experimental findings must be reconciled with clinical studies, where other institutions have reported more FSSC in their keratitis patients (3,16,32) Clearly, in vitro experiments are limited in simulating all of the conditions that predispose patients to Fusarium keratitis.…”
Section: Discussionmentioning
confidence: 99%
“…Bullock et al suggested that exposure of ML to relatively high temperatures caused decreased fungicidal activity and that this contributed to the Fusarium keratitis outbreak (7). Ahearn et al described the attachment of F. solani to contact lenses and subsequent failure to manually clean these lenses to explain the increased incidence of Fusarium keratitis (2). Furthermore, the ML manufacturer has also reported that ML showed reduced biocidal activity under conditions that stimulated noncompliance in a number of ways, including evaporation of the solution, but not under the conditions recommended for its use (19).…”
mentioning
confidence: 99%